ORGANIZATIONAL, PEDAGOGICAL, AND PSYCHOLOGICAL CHARACTERISTICS OF ORGANIZING EDUCATION FOR MENTALLY DISABLED CHILDREN - Abdumutal Olimovich Abdunazarov (Web of Journals Publishing, 2024)
This article explores the organizational, pedagogical, and psychological characteristics of organizing education for mentally disabled children. In the process of effectively organizing special education for these children, individual approaches, the creation of a developmental environment, and the formation of knowledge based on special methodologies are critical issues. The article extensively highlights the organizational foundations of this type of education, the technologies used in establishing the pedagogical process, and the consideration of students' psychological states.
Keywords: Mentally disabled children, special education, pedagogical approach, psychological characteristics.